Imunização de camundongos com antígenos de lisado total (NLA) e de excreção-secreção (NcESA) de Neospora caninum associados com oligodeoxinucleotídeo CpG como adjuvante - Ribeiro, Dâmaso Pacheco (2008)
Neospora caninum is an apicomplexan parasite that causes neuromuscular diseases in dogs and abortion in cattle worldwide, leading to significant economic losses. Studies using murine models have contributed to characterize novel antigens and strategies for successful protocols of vaccination. CpG oligodeoxynucleotides (ODN) have shown to be potent immunoadjuvants for several pathogens, but there is limited information concerning its utilization in vaccination for neosporosis. This study aimed to evaluate the potential of Neospora lysate antigen (NLA) or excreted-secreted antigen (NcESA) combined with CpG-ODN in inducing enhanced immune response and protection against N. caninum infection in mice. Six groups of C57BL6 mice were vaccinated subcutaneously three times at 2-week intervals with NLA, NLA+CpG, NcESA, NcESA+CpG, CpG (adjuvant control) or PBS (infection control). Serological assays showed an increased IgG2a response in groups of animals immunized with either antigen plus adjuvant and elevated levels of the IgG1 isotype in those presenting antigen preparations alone. Splenocyte proliferative responses upon antigen stimulation in vitro were higher in groups immunized with either antigen plus CpG, with increased IL-12 production, but mice immunized with NcESA or NcESA+CpG exhibited higher IFN-g levels and IFN-g/IL-10 ratio. After a month of the 3rd booster and challenge with 2 x 107 N. caninum tachyzoites, mice vaccinated with NLA+CpG or NLA alone had lower morbidity score and body weight changes in comparison to other groups, and no animal succumbed to infection. In contrast, mice vaccinated with NcESA+CpG or NcESA exhibited the highest morbidity scores, body weight changes and mortality rates after challenge, associated with a greater brain parasite burden determined by PCR and immunohistochemistry. In conclusion, CpG-ODN was able to induce an increased Th1- type immune response as determined by higher levels of IgG2a than IgG1 for either antigen, NLA or NcESA, and a strong cellular immune response associated with high levels of IFN-g was related to the NcESA antigen rather than the adjuvant used. Also, vaccination with NLA+CpG or NLA alone resulted in total protection of mice, while NcESA alone or combined with CpG became mice more susceptible to parasite challenge.